The predicting effects of depression and self-esteem on suicidal ideation among adolescents in Kuala Lumpur, Malaysia - Chin, Wen Cong; Wu, Shin Ling * (Faculty of Medicine, University of Malaya, 2020)
Background: In Malaysia, the prevalence of adolescents’ suicidal ideation has increased over the years. Therefore, it is crucial to investigate the predictors of suicidal ideation among adolescents. Hence, the aim of this study was to examine the predicting effects of depression and self-esteem on suicidal ideation among Malaysian adolescents. In addition, the relationships between depression, self-esteem, and adolescents’ suicidal ideation were explored as well. Methods: By using a multistage cluster sampling method, a cross-sectional study was conducted in secondary schools in Kuala Lumpur, Malaysia. The participants were comprised of 852 adolescents (51% males and 49% females) aged 13-17 years old who completed self-administered questionnaires. Pearson’s Correlation analysis was used to analyse the relationships among depression, self-esteem, and adolescents’ suicidal ideation, while Standard Multiple Regression analysis was used to examine the predicting effects of depression and self-esteem on adolescents’ suicidal ideation. Results: Depression had a positive correlation with adolescents’ suicidal ideation (r = .290, p < .001), while self-esteem had a negative correlation with adolescents’ suicidal ideation (r = -.283, p < .001). Results also showed that both depression (β = .200, p < .001) and self-esteem (β = -.186, p < .001) significantly predicted adolescents’ suicidal ideation. Conclusion: The study found that depression is a risk factor, while self-esteem is a protective factor of adolescents’ suicidal ideation.